THE ROLE AND IMPORTANCE OF PROFESSIONAL MOTIVATION IN TEACHERS’ ACTIVITIES - L. A. Jabarova; M. S. Pulatova (Modern American Journals, 2025)
The article emphasizes that the effectiveness of pedagogical activity in the modern education system is directly linked to the professional motivation of teachers. Professional motivation is related to the teacher's attitude toward the profession, creative activity, and desire for self-actualization, all of which contribute to improving the quality of education. In Uzbekistan's education reforms, material and moral incentives (such as increasing salaries and professional development programs) are being implemented to enhance motivation. Empirical research findings show that highly motivated teachers use innovative methods, increase students' cognitive engagement, and reduce professional burnout. Continuous monitoring and reinforcement of professional motivation will help improve the quality of education.
Keywords: Professional motivation, pedagogical activity, teacher effectiveness, motivation theories, internal and external factors, educational quality, professional burnout, educational reforms, Uzbekistan, innovative methods.